New variety adopted: Mayi Plus II - CGIAR Research Program on Maize (2018)
Mayi Plus II was one of the varieties selected from trials established over the last 2 years across many areas of Haiti. In 2018, seed increases have already been carried out. Haitian farmers are producing and disseminating their own improved seed..